How Multilingual Filipinos Learn Spanish as a Foreign Language: Some Crosslinguistic Considerations - Sibayan-Sarmiento, Anna (Philippine Humanities Review, 2019)
The inclusion of foreign language units in the Philippine high school curriculum calls for an urgent examination of how we multilingual Filipinos learn the not-so-foreign Spanish as a foreign language (FL). Filipinos have been learning Spanish since the 1950s, yet little is still known about the learning of a language that is not exactly foreign to us. The present study, which considers adolescent learners who not only speak the country’s two official languages but other languages as well, aims to shed light on how multilingual Filipinos learn Spanish as FL by examining how language similarity affects FL learning as evidenced by productions of crosslinguistic influence (CLI) in speech. Monologic and classroom interaction data were gathered from four groups of participants of different proficiency levels. Results were very interesting: English, Filipino, and Romance languages contributed to the majority of CLI production in terms of vocabulary, where English and Filipino were mostly manifested in content words, while Romance languages in function words. For grammar and syntax, English was dominant, while for pronunciation, it was both Filipino and English. Influence from other Philippine languages was scarce, if at all. In light of these findings, this paper concludes with insights on current FL teaching practices. KEYWORDS: Spanish as a foreign language, foreign language learning, adult language acquisition, language contact, crosslinguistic influence